Parental Perceptions of Gadget Used in Children Aged 4-6 Years in Tarumajaya District - Ramandhini, Rifdah Fauziah; Rahman, Taopik; Gandana, Gilar (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Rapid technological developments have encouraged the use of gadgets among various groups, including early childhood. This study aims to describe parental perceptions of gadget use in children aged 4–6 years. The study used a descriptive quantitative approach with a survey technique of 33 parents in Tarumajaya District. The data collection instrument was a Guttman scale questionnaire which was analyzed descriptively using. The results showed that the majority of parents had a negative perception of the impact of gadget use, especially related to behavioral, social, and emotional disorders in children. However, some parents also acknowledged the positive benefits of gadgets in supporting children's cognitive, language, and creative development, as long as their use is limited and properly supervised. These findings emphasize the importance of parental knowledge and involvement in guiding gadget use to minimize negative impacts and optimize benefits.